An empowerment‐based cognitive behavioural therapy for persons with mild cognitive impairment and insomnia: Protocol for a mixed‐method pilot study. (13th January 2021) - Li, Polly W. C.; Yu, Doris S. F.; Wong, Cathy W. Y.
Abstract: Aim: This study aims to examine the feasibility and effects of an empowerment‐based cognitive behavioural therapy for insomnia on sleep, cognitive outcomes, and health‐related quality of life in persons with mild cognitive impairment and insomnia. Study design: This mixed‐methods study comprises a pilot randomized controlled trial and an exploratory qualitative study. Methods: A total of 60 community‐dwelling patients aged ≥50 years with mild cognitive impairment and self‐reported sleep complaints will be recruited from the community centres for older people operated by two non‐governmental organizations in Hong Kong. The participants will be randomly allocated to intervention or control groups, which will receive the empowerment‐based cognitive behavioural therapy for insomnia and usual care respectively. We hypothesize that the cognitive behavioural therapy for insomnia intervention featuring an empowerment‐based approach can improve sleep and cognitive function among patients with mild cognitive impairment. A subsample of 10 participants from the intervention group will be invited to take part in a qualitative interview to obtain more in‐depth comments about the feasibility and acceptability of the intervention. Ethical approval was obtained on 2 November 2020. This study is supported by the Seed Fund for Basic Research from the University of Hong Kong on 4 September 2020. Discussion: This study will address a neglected risk factor for cognitive decline in persons with mild cognitive impairment. The theoretical integration of empowerment and cognitive model of behavioural changes may inform a wider and more successful application of cognitive behavioural therapy techniques for people with compromised cognitive ability and insomnia. Impact: This study will also advance our knowledge on the role of sleep on persons with mild cognitive impairment and generate relevant empirical evidence to inform the care of this vulnerable cohort to affect a worldwide reduction in social, economic and healthcare burdens associated with cognitive impairment. Clinical Trial Registration: This study has been registered at ClinicalTrials.gov (NCT04635085). 摘要: 目的: 本研究旨在探讨基于授权的认知行为疗法对轻度认知障碍和失眠症患者的失眠情况、认知结果和健康相关生活质量的可行性和效果。 研究设计: 此混合方法研究包括一项试验性随机对照试验和一项探索性定性研究。 方法: 未来, 两个非政府组织的老年人社区中心将在香港招募60名年龄在50岁以上的轻度认知障碍和自我报告存在失眠情况的社区居民。参与者将被随机分配到干预组或对照组, 分别接受基于授权的失眠认知行为治疗和常规护理。我们假设基于授权的失眠干预认知行为疗法可以改善轻度认知障碍患者的睡眠和认知功能。干预组将邀请10名参与者参加次定性访谈, 希望其就干预的可行性和可接受性等内容发表意见。此项目于2020年11月2日获得伦理批准。本研究由香港大学基础研究种子基金供资, 供资时间为2020年9月4日。 讨论: 本研究将可用于消除造成轻度认知障碍患者认知能力下降的风险因素, 尽管该风险因素目前被人们忽视。授权与行为改变认知模式的理论整合可为认知能力受损和失眠患者提供更广泛和更成功的认知行为治疗技术。 影响: 除上述内容外, 本研究还将帮助人们理解睡眠对轻度认知障碍患者的作用, 产生相关的经验证据, 要求给与这一弱势群体护理, 从而在全球范围内减少与认知障碍相关的社会、经济和医疗负担。